MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF BAGI PESERTA DIDIK - Setiawan, Herdi; Mudjiran, Mudjiran (Study program PGSD FKIP Universitas Bung Hatta, 2022)
This paper intends to review the importance of creating a conducive learning environment for students so that learning objectives can be achieved. The purpose of this paper is to provide insight to the parties who take part in the world of education to better understand the following: the problem of the concept of a learning environment and the concept of a conducive learning environment. cooperation and conformity between the physical and social conditions of the learning environment and learning participants, in this case students and teachers, is needed to build a conducive learning environment. To develop a successful learning environment in the classroom, both learning environments must be maximized. The method used in this paper is descriptive qualitative and literature study. The result is seven recommendations that schools, teachers and communities can make in creating a conducive learning environment.